KARAKTERISTIK TEPUNG LIMBAH AMPAS KELAPA PASAR TRADISIONAL DAN INDUSTRI VIRGIN COCONUT OIL (VCO) - Diana Widiastuti; Ade Heri Mulyati; Muthia Septiani (EKOLOGIA, 2015)
Coconut processing industry produces a by-product or shredded coconut husks limbahberupa. The main advantage of the dregs of coconut food fiber is high, which proved instrumental in the prevention and control of various chronic diseases such as colon cancer, heart attack, hypertension, stroke and diabetes mellitus. This research aims to produce products made from flour, coconut dregs have a good nutritional quality and food high in fiber so it is expected to become a functional food ingredients. This research use the sample waste dregs of coconut derived from shredded coconut seller in the traditional markets of coconut husks and waste from industrial Virgin Coconut Oil (VCO), then waste coconut husks that are washed, boiled, dried and milled into flour so that the coconut husks. Based on data proksimat the flour coconut pulp market has food and fiber carbs are lower while levels of protein, fat and vast grounds higher than the flour coconut husks VCO.Analysis of microbiological by-product of coconut flour shows VCO has sanitation and food security is better when compared to the dregs of coconut flour market.Key words: Waste, Coconut Dregs Of Flour, Proksimat, Microbiology